Peran Sumber Daya Manusia Terhadap Efektivitas Pemasaran Biro Wisata - Ryan Chandi Alfianto; Sudarmadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This article aims to analyze the role of human resources (HR) in enhancing marketing effectiveness in the travel agency industry. The research highlights that quality HR is a crucial element in implementing effective marketing strategies, as they are directly involved in interactions with consumers and in conveying information about tourism products. The method used in this study is a qualitative approach, with data collection techniques including in-depth interviews and observations at various tourist locations. The findings indicate that the development of HR competencies through ongoing training and education is essential to meet the demands of the ever-evolving tourism industry. Additionally, the use of information technology is also considered vital for expanding marketing reach and increasing the appeal of tourism products. These findings are expected to provide insights for travel agencies in optimizing the role of HR to achieve better marketing success.